Designing SMART-PJU Based on LoraWAN for Rural Light System - Pratama, Legenda Prameswono (Eksergi, 2023)
In the industrial era 4.0, every industrial tool or equipment and building already uses automation via IoT, especially in public street lighting. Using a SMART-PJU-based LoraWAN system can minimize electrical energy use by using dimmer schedule control and ON/OFF schedule control. Using a dimmer schedule for PJU lights, the energy is set maximum of 10 amperes depending on the dimmer module used. The SMART-PJU has a LoRa module to control and monitor them via a wireless network. This research used the LoRa-EBYTE E32-DTU(915L20) module as the data sender and receiver. LoRa-EBYTE E32-DTU(915L20) with a frequency of 915 MHz to 931 MHz and an RS232/RS485 connector. The furthest distance that can be reached during testing at the Jakarta Global University campus, with a frequency of 922 MHz, is 450 meters, 344 meters, and 215 meters at three different points. The SMART-PJU system can regulate light, ON/OFF control, and ON/OFF schedule and can see the on or off status of the digital output on the Arduino. To ensure the module is on or off. Furthermore, it can monitor electricity usage in the PJU, such as power, voltage, current, power factor, and frequency, via the PZEM-016 sensor. The comparison value using the dimmer schedule at 12 hours is 375.62 Wh without the dimmer, 1085.04 Wh, and the average comparison error value of the PZEM-016 sensor reading with a multimeter is 0.1 current, 0.009 voltage, 0.3 power at each dimmer setting from 20 to 80. All data are obtained and viewed using Node-red software. By using Node-red software, users can control and monitor easily because Node-red uses language and displays that are easy for users to understand.